2015
DOI: 10.5194/acp-15-10033-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2050 climate change on North American wildfire: consequences for ozone air quality

Abstract: Abstract. We estimate future area burned in the Alaskan and Canadian forest by the mid-century (2046-2065) based on the simulated meteorology from 13 climate models under the A1B scenario. We develop ecoregion-dependent regressions using observed relationships between annual total area burned and a suite of meteorological variables and fire weather indices, and apply these regressions to the simulated meteorology. We find that for Alaska and western Canada, almost all models predict significant (p < 0.05) incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 107 publications
1
34
0
Order By: Relevance
“…This is consistent with previous studies which have found increased sensitivity to surface CO for large VCDs (Bauduin et al, 2017). Yurganov et al (2011) compared IASI VCDs with measurements from three grating spectrometers within a plume from forest and peat fires in central Russia in July-August 2010. They found that the IASI VCDs were biased low compared with the ground-based measurements by an estimate of 1.61 ×10 18 molec cm −2 , or ∼ 35 %, over a sample with a mean IASI CO VCD of 4.7 ×10 18 molec cm −2 .…”
Section: Iasi Co and Nhsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous studies which have found increased sensitivity to surface CO for large VCDs (Bauduin et al, 2017). Yurganov et al (2011) compared IASI VCDs with measurements from three grating spectrometers within a plume from forest and peat fires in central Russia in July-August 2010. They found that the IASI VCDs were biased low compared with the ground-based measurements by an estimate of 1.61 ×10 18 molec cm −2 , or ∼ 35 %, over a sample with a mean IASI CO VCD of 4.7 ×10 18 molec cm −2 .…”
Section: Iasi Co and Nhsupporting
confidence: 90%
“…Due to their spatial and temporal coverage, satellite remote sensing instruments can capture some of this natural variability by estimating emissions and emission factors over various seasons, burning conditions, fuel types, and moisture content. Previous studies using satellite CO, NH 3 , and NO 2 data have assessed the relationship between these species (e.g., Coheur et al, 2009;Krol et al, 2013;Luo et al, 2015;Paulot et al, 2017;Pechony et al, 2013;R'Honi et al, 2013;Yurganov et al, 2011) and have also estimated emissions and emission factors (e.g., Mebust and Cohen, 2014;Mebust et al, 2011;Schreier et al, 2014Schreier et al, , 2015Tanimoto et al, 2015;Whitburn et al, , 2016b. Emission factors have also been estimated using groundbased Fourier transform infrared (FTIR) spectrometers (e.g., Lutsch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intense episodic transport from biomass burning can impact near‐surface observations and lead to deposition of absorbing aerosol on snow and ice surfaces (e.g., Stohl et al, , ). An increasing extent of biomass burning and earlier onset of the burning season, related to increasing global temperatures, will likely have strong impacts on Arctic aerosol in the future (e.g., Y. Kim et al, ; Moritz et al, ; Warneke et al, ; Yue et al, ).…”
Section: Long‐range Transportmentioning
confidence: 99%
“…As listed in Table 2, we conduct the GEOSChem simulations by using the 1986-1990 MERRA fields (for comparison with the 2006-2010 fields) or the preindustrial land use data (1860 vs. the present-day condition for 2000), generally following the previous work of Fu and Tai (2015) and Heald and Geddes (2016). The impacts of climate change on wildfire emissions (Yue et al, 2015) are not considered here.…”
Section: Asynchronous Coupling and Model Experimentsmentioning
confidence: 99%